Female Abbatial Leadership and the Shaping of Communal Identity in Ninth-Century Saxony: The Life of Hathumoda of Gandersheim - Thibaut, Jirki (Journal of Medieval Monastic Studies, 2018)
Abstract By looking at the Life of Hathumoda, a ninth-century biographical account of the first abbess of the female monastery of Gandersheim in Saxony (d. 874), this article examines how women religious in ninth-century Saxony made use of normative legacies to create their own corporate identity through which they could respond to challenges in society. Contrary to what previous scholarship often assumed, the Benedictine portrayal of Hathumoda and her community was not a top-down stimulant aimed at convincing the women religious of Gandersheim to adopt a strictly Benedictine observance, but the result of the community's own attempt to shape a distinctive identity in an increasingly dense and competitive monastic landscape.